Framing Analysis of Rohingya Refugee Reporting in Indonesian Online Media: Perspectives on Humanitarian Crisis and Government Role - Yaqin, Moch Ainul (Al-MUNZIR, 2024)
The increasing intensity of Rohingya refugee arrivals due to ethnic conflicts in Q4 2023 and Q1 2024 has once again drawn the attention of online mass media. The headlines set by several media outlets indicate that this event holds significant news value. The issue of Rohingya refugees has become one of the most prominent humanitarian crises of the 21st century, sparking various reactions and debates worldwide. On one hand, it reflects compassion and solidarity toward humanity, while on the other, it demands a firm stance that upholds national values. This study employs a constructivist paradigm using Robert N. Entman's framing analysis model. The research focuses on how online media frame news about Rohingya refugees as victims of conflict in Myanmar. Six online media outlets were analyzed, including IDN Times (March 5), Detik.com (April 3), Liputan6 (April 13), CNN Indonesia (May 3), Kompas.com (May 7), and Tribunnews (May 7), arranged chronologically by the most recent publication of news on the Rohingya refugee issue. The analysis uses elements of Robert N. Entman's model, comprising Define Problem (problem definition), Diagnose Causes (identifying the problem and its sources), Make Moral Judgement (making moral assessments), and Treatment Recommendation (emphasizing solutions). The findings show that each media outlet's framing influences readers' perceptions differently. Online media generally tend to frame the issue positively regarding the government, portraying its central role as the primary helper. However, Liputan6 takes a more critical approach, encouraging readers to recognize shortcomings and challenges, including violations of local regulations by refugees. Meanwhile, CNN Indonesia opts for a global perspective, helping readers understand the scale of the crisis and the importance of international responses.Keywords: Framing Analysis, Indonesian Online Media, Latest Rohingya News